Medical Image Computing and Computer-Assisted Intervention – MICCAI 2007
DOI: 10.1007/978-3-540-75759-7_79
|View full text |Cite
|
Sign up to set email alerts
|

Online Estimation of the Target Registration Error for n-Ocular Optical Tracking Systems

Abstract: Abstract. For current surgical navigation systems optical tracking is state of the art. The accuracy of these tracking systems is currently determined statically for the case of full visibility of all tracking targets. We propose a dynamic determination of the accuracy based on the visibility and geometry of the tracking setup. This real time estimation of accuracy has a multitude of applications. For multiple camera systems it allows reducing line of sight problems and guaranteeing a certain accuracy. The vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 6 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…In this section, the maximum likelihood [8], spatial stiffness [4], transform of covariance [5], Wiles [7], and Fitzpatrick and West [2] algorithms are briefly explained. Then, it is shown that when FLE has an arbitrary Gaussian distribution, the first three algorithms converge to a unique solution; and when FLE has an identical and isotropic Gaussian distribution, all the algorithms converge to the same solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, the maximum likelihood [8], spatial stiffness [4], transform of covariance [5], Wiles [7], and Fitzpatrick and West [2] algorithms are briefly explained. Then, it is shown that when FLE has an arbitrary Gaussian distribution, the first three algorithms converge to a unique solution; and when FLE has an identical and isotropic Gaussian distribution, all the algorithms converge to the same solution.…”
Section: Methodsmentioning
confidence: 99%
“…Sielhorst et al [5] employed the transform of covariance algorithm, introduced by Hoff and Vincent [6], to calculate the covariance matrix of the transformation parameters as follows:…”
Section: Transform Of Covariance Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In flexible configurations of multi-camera setups and under varying viewing conditions in dynamic scenes, however, a full error description becomes more difficult and cannot easily be interpreted anymore. Also, the real-time description of varying uncertainty in pose estimation has only recently been addressed in more detail ( [17], [2], [10]). Most approaches make use of the covariance matrix as a means of quantifying measurement errors and for the visualization of error ellipsoids.…”
Section: Introductionmentioning
confidence: 99%